2014
DOI: 10.1186/1471-2393-14-323
|View full text |Cite
|
Sign up to set email alerts
|

‘Born before arrival’: user and provider perspectives on health facility childbirths in Kapiri Mposhi district, Zambia

Abstract: BackgroundMaternal mortality remains high in sub-Saharan Africa. Health facility intra-partum strategies with skilled birth attendance have been shown to be most effective to address maternal mortality. In Zambia, the health policy for pregnant women is to have facility childbirth, but less than half of the women utilize the facilities for delivery. ‘Born before arrival’ (BBA) describes childbirth that occurs outside health facility. With the aim to increase our understanding of trust in facility birth care we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 27 publications
(40 reference statements)
3
34
1
4
Order By: Relevance
“…Non-randomised studies have found large impacts of non-monetary incentives on utilisation of health services including HIV counselling and testing [18], prenatal care [8] and immunisation services [7]. However, the factors that influence whether a woman delivers at a facility are often a more complex combination of individual and environmental-level factors than those that may influence whether someone attends shorter, less time-critical health services [20][21][22]. Several studies have noted that the primary barriers in rural areas to delivering at a health facility in sub-Saharan Africa are long distances to health facilities and a lack of transport [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Non-randomised studies have found large impacts of non-monetary incentives on utilisation of health services including HIV counselling and testing [18], prenatal care [8] and immunisation services [7]. However, the factors that influence whether a woman delivers at a facility are often a more complex combination of individual and environmental-level factors than those that may influence whether someone attends shorter, less time-critical health services [20][21][22]. Several studies have noted that the primary barriers in rural areas to delivering at a health facility in sub-Saharan Africa are long distances to health facilities and a lack of transport [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Social and cultural factors including previous successful home deliveries, belief that local herbs speed up labour, belief that women should exhibit endurance during child birth, lack of participation in decision making, ready availability of traditional birth attendants(TBA), and presence of male midwifes in health facilities have also been identified as deterrents to hospital deliveries[8,12,28,30]. …”
Section: Introductionmentioning
confidence: 99%
“…One in every three women aged 15–19 in rural areas is either already a mother or pregnant compared to one in every five in urban areas [42]. Further, women in rural areas are far less likely to seek professional assistance for childbirth due to distance, fewer skilled health care workers, and fewer and poorly equipped health facilities compared to women in urban areas [4347]. Giving birth without skilled attendance is associated with greater risk of mortality [48].…”
Section: Discussionmentioning
confidence: 99%